A Study of Green Infrastructure in European Cities: Opportunities and possibilities: A Systematic Review and Meta-Analysis - Jenan Hussein; Peter Kumble; Henry W.A Hanson IV (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Green infrastructure (GI) is generally defined as a network of natural and semi-natural regions that has been sensitively developed and managed to provide an array of ecosystem services and improve people’s well-being. Across Europe, the notion of GI has had a robust association with the the impacts of climate change, multifunctionality, and green growth; this is especially true over the past ten years, from 2012 to 2022. This has resulted in a broad-based agenda on policy and research with vast differences, targeting a variety of themes and cultures. The systematic review and meta-analysis conducted in this paper present an up-to-date review of the main attributes of GI-related research and the implications for the member states within the European Union (EU). GI-related concepts, thematic clusters, and the main priorities within the research were considered in our review. Due to the ambiguity of the definition of GI, a broad diversity of research goals and published output are discussed. It was also seen that green spaces situated within urban areas and their related ecosystem services are the most common topics in the literature. Based on this, we recommend that an in-depth integration of the goals pertaining to nature conservation be conducted to understand how GI may pertain towards sustainable transitions in and outside the city.